Solution-processed all-oxide bulk heterojunction solar cells based on CuO nanaorod array and TiO2 nanocrystals. (28th March 2018) - Wu, Fan; Qiao, Qiquan; Bahrami, Behzad; Chen, Ke; Pathak, Rajesh; Tong, Yanhua; Li, Xiaoyi; Zhang, Tiansheng; Jian, Ronghua
Abstract: We present a method to synthesize CuO nanorod array/TiO2 nanocrystals bulk heterojunction (BHJ) on fluorine-tin-oxide (FTO) glass, in which single-crystalline p-type semiconductor of the CuO nanorod array is grown on the FTO glass by hydrothermal reaction and the n-type semiconductor of the TiO2 precursor is filled into the CuO nanorods to form well-organized nano-interpenetrating BHJ after air annealing. The interface charge transfer in CuO nanorod array/TiO2 heterojunction is studied by Kelvin probe force microscopy (KPFM). KPFM results demonstrate that the CuO nanorod array/TiO2 heterojunction can realize the transfer of photo-generated electrons from the CuO nanorod array to TiO2 . In this work, a solar cell with the structure FTO/CuO nanoarray/TiO2 /Al is successfully fabricated, which exhibits an open-circuit voltage ( V oc ) of 0.20 V and short-circuit current density ( J sc ) of 0.026 mA cm −2 under AM 1.5 illumination. KPFM studies indicate that the very low performance is caused by an undesirable interface charge transfer. The interfacial surface potential (SP) shows that the electron concentration in the CuO nanorod array changes considerably after illumination due to increased photo-generated electrons, but the change in the electron concentration in TiO2 is much less than in CuO, which indicates that the injection efficiency of the photo-generated electrons from CuO to TiO2 is not satisfactory, resulting in an undesirable J sc in the solar cell. The interface photovoltage from the KPFM measurement shows that the low V oc results from the small interfacial SP difference between CuO and TiO2 because the low injected electron concentration cannot raise the Fermi level significantly in TiO2 . This conclusion agrees with the measured work function results under illumination. Hence, improvement of the interfacial electron injection is primary for the CuO nanorod array/TiO2 heterojunction solar cells.